Design of a high performance machine with an innovative cooling method to achieve the FreedomCar 2020 traction machine targets - Walker, Adam (2017)
The thesis details a successful attempt at meeting the US Department of Energy FreedomCar 2020 targets. These targets include a set of challenging specifications for traction machines for hybrid electric vehicle applications. Previously the main barrier to achieving these targets was designing a machine which could meet the high speed efficiency targets whilst not sacrificing attaining the peak torque. The need for this high performance across a wide speed range is to allow for direct drive electric vehicles. The thesis covers the design process for a machine to reach these targets from the very beginning, comparing machine topologies and technologies based on qualitative indices to decide which is the most appropriate. Next, interior permanent magnet machines are designed for these targets using the current technology standards and their shortcomings are highlighted. This leads into a permanent magnet assisted synchronous reluctance design, which improved the high speed efficiency but performed worse thermally. A large section of the thesis is dedicated to the innovative thermal management method used to push the boundaries of efficiency in this application. This discussion of the cooling method includes experimental proof of its potential and validated simulations supplementing this into the further machine design. Finally a more in-depth optimisation is performed for the electromagnetic design, with the new less restrictive thermal limits, which produces the ideal design, a permanent magnet assisted synchronous reluctance motor, for reaching the FreedomCar 2020 traction machine targets.